Determinants of efficiency of Islamic banks : Indonesian evidence - Bayuny, Ahmad Fadlur Rahman (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
This research attempts to investigate the efficiency of Islamic banks in Indonesia and its determinants over the period of 2004-2014. There are 11 Full Islamic banks that is taken for the sample. The method applied in the first stage are Data Envelopment Analysis (DEA), under the assumption of Constant Return to Scale (CRS). This study utilizes 2 inputs (fixed asset and deposits) and one output (financing income) based on intermediation approach. Panel data regression method is exhibited for the second stage analysis. The research finds that the efficiency scores of Islamic banks in Indonesia ranged from 61.4% to 96.4% between 2004-2014. The DEA analysis stated that the overall efficiency of Islamic banks in Indonesia is 75.6%. The result from second stage analysis regression suggest that the efficiency is negatively associated with the growth of GDP, log natural of exchange rate and trade freedom index. The empirical result showed that the positive relationship was found between Islamic banks efficiency and profitability, financing intensity, capitalization, non-financing expenses over total asset ratio.